2010
DOI: 10.1002/pros.21178
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical examination of the mTORC1 pathway in high grade prostatic intraepithelial neoplasia (HGPIN) and prostatic adenocarcinomas (PCa): A tissue microarray study (TMA)

Abstract: mTOR inhibitors may be an effective treatment for HGPIN and PCa. The extent of mTOR expression in an individual patient would determine the effective use of mTOR inhibitors as a potential therapeutic strategy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
15
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 32 publications
6
15
1
Order By: Relevance
“…mTOR was detected mostly in the cytoplasm of epithelial cells from benign glands and cancer cells of tumor foci, with low or undetectable expression in stromal cells (Fig. 6A), which is consistent with previous studies (Dai et al 2009;Evren et al 2010;Sutherland et al 2014). No difference in mTOR cytoplasmic staining intensity between peri-tumoral and tumor samples was found (Supplemental Fig.…”
Section: Nuclear Mtor Levels Correlate With Pca Progressionsupporting
confidence: 91%
See 1 more Smart Citation
“…mTOR was detected mostly in the cytoplasm of epithelial cells from benign glands and cancer cells of tumor foci, with low or undetectable expression in stromal cells (Fig. 6A), which is consistent with previous studies (Dai et al 2009;Evren et al 2010;Sutherland et al 2014). No difference in mTOR cytoplasmic staining intensity between peri-tumoral and tumor samples was found (Supplemental Fig.…”
Section: Nuclear Mtor Levels Correlate With Pca Progressionsupporting
confidence: 91%
“…The mTOR signaling pathway is hyperactivated in PCa tumors compared with peri-tumoral or benign prostate tissues (Kremer et al 2006;Evren et al 2010;Sutherland et al 2014). In fact, alterations leading to hyperactivation of mTOR and its upstream regulators (PI3K/Akt), such as loss of PTEN, are among the most frequent genomic alterations in metastatic CRPC (Taylor et al 2010;Grasso et al 2012;Robinson et al 2015;Kumar et al 2016).…”
mentioning
confidence: 99%
“…mTOR is closely associated with the genesis and development of cancer. Previous studies have demonstrated that mTOR protein expression is significantly upregulated in various types of cancer tissue, including PC, liver cancer, cervical cancer, colorectal cancer, lung adenocarcinoma, esophageal squamous carcinoma, non-small cell lung cancer and extra hepatic bile duct carcinoma (25,28). The results of the present study demonstrated that treatment with cucurbitacin E induced mTOR protein expression inhuman PC cells.…”
Section: Discussionsupporting
confidence: 71%
“…Two recent reports using TMAs and quantitative IHC, for the study of malignant peripheral nerve sheath tumours [53] and malignant pleural mesothelioma [54], showed the approach to be an effective high-throughput tool for the investigation of protein expression. Moreover, multiplex IHC and TMAs were successfully used together to examine the mTORC1 pathway in high-grade prostate intraepithelial neoplasia (HGPIN) and prostatic adenocarcinomas (PCa) [55].…”
Section: Immunohistochemical Staining Of Tissue Microarraysmentioning
confidence: 99%